NILAI-NILAI DALAM PEMENTASAN CALONARANG BASUR SEBAGAI PENGUATAN KARAKTER WARGA DESA KELIKI DALAM PERSPEKTIF PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Praditya, I Putu Eka; Sujana, I Putu Windu Mertha (Program Studi PPKn Universitas Pendidikan Ganesha, 2026)
This research aims to determine (1) the understanding of the Keliki Village community, particularlythe younger generation, of the values contained in Calonarang Basur; (2) the role of CalonarangBasur in strengthening the character of the Keliki Village community; and (3) the analytical valueswithin Calonarang Basur as a means of character reinforcement for the Keliki Village community.This research employed a qualitative method with a descriptive-analytical approach. The qualitativeresearch involved data collection from various sources, including interviews, observations, anddocumentation. The research subjects consisted of traditional leaders, Calonarang artists, theyounger generation, and the Keliki Village community. Data were collected through observation, indepth interviews, and documentation. The results indicate that: (1) the community’s understanding,particularly among the younger generation, of the values of Calonarang Basur is generally adequate,although some youths have not yet fully comprehended its philosophical meanings; (2) CalonarangBasur plays an important role in strengthening community character through the cultivation ofreligious values, responsibility, discipline, togetherness, and respect for customary norms; and (3)the analytical values contained in Calonarang Basur can be interpreted as a form of charactereducation based on local wisdom that is relevant to the lives of the Keliki Village community.